Firewall: Health Essentials for Ministers and Their Families - Flynn, James T. (Christian education journal, 2009)
Ministerial formation is an essential function of Christian education. Its goal is for ministers and their families to experience a lifetime of fruitful service. When formation does not take into account forces of deformation commonly experienced in ministry, the result is malformation that leads to failure under stress with devastating consequences. Statistics suggest that ministers are not adequately prepared to handle common stressors encountered in ministry environments. At least four common stressors in ministry should be addressed in curricular design for ministerial formation to build a “firewall” of protection for ministers and their families to ensure better long-term outcomes.